Author, reviewer and translator: Katherine Mansfield's place in literary culture - Jones, Katie L. (2021)
This thesis extends and revises current assessments of Katherine Mansfield’s engagements with literary culture and the literary marketplace. Historical examinations of Mansfield’s literary and professional development have largely overlooked the impressive breadth of her involvement with the literary field in favour of accentuating her role as a short story specialist. Building on recent attempts by Mansfield scholars to encourage a renewed critical interest in her wider investments in the literary marketplace, this thesis examines some of her most neglected creative and critical contributions. These include her early ‘child verses’, her 1908-9 musical performance pieces, her 1919-20 translations of the personal writings of Anton Chekhov, and her critical and editorial contributions to Rhythm and The Athenaeum. By offering the most nuanced contextualisation to date of her investments as a professional author, reviewer and translator, this thesis looks to provide a multifaceted account of Mansfield’s place in literary culture and her literary legacy.